Utilisation of IGCC slag and clay steriles in soft mud bricks (by pressing) for use in building bricks manufacturing - Acosta, A; Iglesias, I; Aineto, M; Romero, M; Rincón, J.Ma (Waste management (Elmsford), 2002)
The subject of this study is the application to the construction of soft mud bricks (also known as pressed bricks), both green and heat-treated bodies, built from raw materials from Santa Cruz de Mudela, Ciudad Real, and IGCC slag from the power central of Puertollano (Ciudad Real, Spain). For this purpose, industrial level tests have been performed: the production of these kind of bricks from mixes of waste from ores of construction clays and to significant fraction of different ratios and clay granulometries mixed with IGCC slag. The results of this experimentation suggests that not only can IGCC slag be applied to a ceramic process, but also its use gives several advantages, as water and energy savings, as well as improvements on the final properties of products.